2009
DOI: 10.1002/cphc.200800704
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Resonance‐Based Generation of Cathodic Photocurrent at Electrodeposited Gold Nanoparticles Coated with TiO2 Films

Abstract: Reversed photoresponse: Indium tin oxide (ITO)/Au nanoparticle (NP)/TiO(2) electrodes (see picture) exhibit cathodic photocurrents and positive photopotentials under visible light, whereas ITO/TiO(2)/Au NP electrodes show an inverted response. This behavior indicates that electron transfer occurs from the plasmon-excited Au NPs to the TiO(2) film. An enhanced O(2) photoreduction activity is found for ITO/Au NP/TiO(2)/Pt electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 27 publications
(17 reference statements)
6
87
1
Order By: Relevance
“…Mass production of this technology requires high reliability and long lifetime Electrodeposition of metal nanoparticles usually involves an electrically assisted reduction of metal cations in a solution environment. Electrodeposition of Ag nanoparticles for plasmonic light enhancement for PV devices has been reported [83,84] . Electrodeposited metal nanoparticles can be relatively small in size but densely packed.…”
Section: Random Structuresmentioning
confidence: 99%
“…Mass production of this technology requires high reliability and long lifetime Electrodeposition of metal nanoparticles usually involves an electrically assisted reduction of metal cations in a solution environment. Electrodeposition of Ag nanoparticles for plasmonic light enhancement for PV devices has been reported [83,84] . Electrodeposited metal nanoparticles can be relatively small in size but densely packed.…”
Section: Random Structuresmentioning
confidence: 99%
“…First, Tatsuma et al [37,38,45] and other workers [42,46] proposed that the photoexcited electrons in the metal nanoparticles transferred from the metal particle to the TiO2 conduction band since the photoresponse of these metal-TiO2 diode structures was consistent with the absorption spectra of Au or Ag nanoparticles. Second, Kamat et al [43,44] and Li et al [47] have suggested that the noble metal nanoparticles act as electron sinks or traps in the metal-TiO2 diode structures to accumulate the photogenerated electrons, which could minimize charge recombination in the semiconductor films.…”
Section: Review Of Metal-insulator-metal (Mim) Diodesmentioning
confidence: 94%
“…However, in these recent metal-TiO2 Schottky diode structures [37][38][39][40][41][42][43][44][45][46][47], it would appear that the barrier layer was actually quite a bit thicker than 10 nm (probably in excess of 1 um) and further details was unable to be found in these papers. Semi-classical models did not account for non-equilibrium energy distributions of carriers, or do so through a localize lattice temperature.…”
Section: Theoretical Modeling Of Ag-tio2-ti Mim Diodesmentioning
confidence: 97%
“…The transfer of photoexcited electrons from a gold particle to the conduction band of titanium dioxide has been put forward by Tian and Tatsuma. 20,21 Their work demonstrates the development of anodic photocurrents on TiO 2 films loaded with Au nanoparticles, whose intensity correlates with the extinction spectrum of the nanostructure under visible irradiation and becomes inhibited in the presence of an acceptor (O 2 ) in solution. However, the clearest evidence of the electron transfer from gold NPs to the conduction band of TiO 2 was obtained by Furube and coworkers who observed a transient absorption of electrons in the conduction band of TiO 2 at 3440 nm after light absorption by the surface plasmon resonance band, SPR, of gold NPs.…”
Section: Introductionmentioning
confidence: 97%